Quantitative reconstitution of yeast RNA processing bodies - Simon L. Currie; Wenmin Xing; Denise Muhlrad; Carolyn J. Decker; Roy Parker; Michael K. Rosen (2023)
Many biomolecular condensates appear to form through liquid–liquid phase separation (LLPS). Individual condensate components can often undergo LLPS in vitro, capturing some features of the native structures. However, natural condensates contain dozens of components with different concentrations, dynamics, and contributions to compartment formation. Most biochemical reconstitutions of condensates have not benefited from quantitative knowledge of these cellular features nor attempted to capture natural complexity. Here, we build on prior quantitative cellular studies to reconstitute yeast RNA processing bodies (P bodies) from purified components. Individually, five of the seven highly concentrated P-body proteins form homotypic condensates at cellular protein and salt concentrations, using both structured domains and intrinsically disordered regions. Combining the seven proteins together at their cellular concentrations with RNA yields phase-separated droplets with partition coefficients and dynamics of most proteins in reasonable agreement with cellular values. RNA delays the maturation of proteins within and promotes the reversibility of, P bodies. Our ability to quantitatively recapitulate the composition and dynamics of a condensate from its most concentrated components suggests that simple interactions between these components carry much of the information that defines the physical properties of the cellular structure.